Comparative diabetogenic action of the hypophysis from various animals - Houssay, Bernardo Alberto (1942)
The role of the anterior portion of the hypophysis in the production or intensification of diabetes was discovered in this Institute in 1929 and 1930 and since then has been studied continuously. An abstract of this work up to 1935 was published by Houssay in 1936. Some of the extracts of anterior hypophysis in animals without hypophysis and pancreas and with mild diabetes, intensified the hyperglycemia and glycosuria to a degree exceeding the intensity of the diabetes associated with pancreatectomy alone. This was observed in the toad (Houssay and Biasotti, 1930), and in the dog (Houssay and Biasotti, 1932; Houssay, Biasotti, and Rietti, 1932; Houssay, Biasotti, Di Benedetti, and Rietti, 1932). These latter observations suggested a possible method of biological assay of the diabetogenic factor. The present experiments were undertaken to demonstrate the relative potency of the diabetogenic principle in extracts of the anterior hypophysis from various species.